C60 Fullerenes Diminish Muscle Fatigue in Rats Comparable to N-acetylcysteine or β-Alanine - Vereshchaka, Inna V.; Bulgakova, Nataliya V.; Maznychenko, Andriy V.; Gonchar, Olga O.; Prylutskyy, Yuriy I.; Ritter, Uwe; Moska, Waldemar; Tomiak, Tomasz; Nozdrenko, Dmytro M.; Mishchenko, Iryna V.; Kostyukov, Alexander I. (Frontiers in Physiology, 2018)
The aim of this study is to detect the effects of C60 fullerenes, which possess pronounced antioxidant properties, in comparison with the actions of the known exogenous antioxidants N-acetylcysteine (NAC) and β-Alanine in terms of exercise tolerance and contractile property changes of the m. triceps surae (TS) during development of the muscle fatigue in rats. The electrical stimulation of the TS muscle during four 30 min series in control rats led to total reduction of the muscle contraction force. Furthermore, the effects of prior intraperitoneal (i.p.) or oral C60FAS application and preliminary i.p. injection of NAC or β-Alanine on muscle contraction force under fatigue development conditions is studied. In contrast to control rats, animals with C60FAS, NAC or β-Alanine administration could maintain a constant level of muscle effort over 5 stimulation series. The accumulation of secondary products and changes in antioxidant levels in the muscle tissues were also determined after the fatigue tests. The increased levels of lactic acid, thiobarbituric acid reactive substances and hydrogen peroxide after stimulation were statistically significant with respect to intact muscles. In the working muscle, there was a significant (p < 0.05) increase in the activity of endogenous antioxidants: reduced glutathione, catalase, glutathione peroxidase and superoxide dismutase. Treated animal groups showed a decrease in endogenous antioxidant activity relative to the fatigue-induced animals (P < 0.05). Oral C60FAS administration clearly demonstrated an action on skeletal muscle fatigue development similar to the effects of i.p. injections of the exogenous antioxidants NAC or β-Alanine. This creates opportunities to oral use of C60FAS as a potential therapeutic agent. Due to the membranotropic activity of C60 fullerenes, nontoxic C60FAS has a more pronounced effect on the prooxidant-antioxidant homeostasis of muscle tissues in rats.